2014
DOI: 10.1039/c4tx00097h
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cardiac mitochondrial oxidative stress and dysfunction induced by arsenic and its amelioration by diallyl trisulphide

Abstract: Mitochondria are the particular target of arsenic (As) in the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…iAs is a multi-target toxin that acts through a variety of mechanisms. In various cell types, exposure to iAs III has been linked to defects in mitochondrial function, including damage to mitochondrial DNA, increased production of reactive oxygen species, decreased expression of Krebs cycle enzymes, and decreased mitochondrial membrane potential (Partridge et al 2007; Sumedha and Miltonprabu 2015; Prakash et al 2015). Fu and coworkers were the first to show that a prolonged (96-h ) iAs III exposure suppresses mitochondrial respiration in the INS-1 832/13 β-cell line while inhibiting GSIS (Fu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…iAs is a multi-target toxin that acts through a variety of mechanisms. In various cell types, exposure to iAs III has been linked to defects in mitochondrial function, including damage to mitochondrial DNA, increased production of reactive oxygen species, decreased expression of Krebs cycle enzymes, and decreased mitochondrial membrane potential (Partridge et al 2007; Sumedha and Miltonprabu 2015; Prakash et al 2015). Fu and coworkers were the first to show that a prolonged (96-h ) iAs III exposure suppresses mitochondrial respiration in the INS-1 832/13 β-cell line while inhibiting GSIS (Fu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is a naturally occurring element in the earth’s crust, which is mostly in the form of trivalent or pentavalent compounds in the natural world. Exposure to arsenic may cause many diseases, such as diabetes, cardiovascular diseases, and kinds of cancers. International Agency for Research on Cancer (IARC) has identified arsenic and its compounds as explicit human carcinogens. , Excessive arsenic content in water resources is one of the important ways for human arsenic exposure. With the rapid development of industries, a large amount of high-arsenic wastewater was discharged into rivers and lakes; arsenic contamination in drinking water has been a global health problem for the past few decades. Moreover, arsenic is also emitted into the environment by burning arsenic coal, , leading to excessive exposure of arsenic to the inhabitants of relevant areas.…”
Section: Introductionmentioning
confidence: 99%
“…41 It has been suggested that the loss of mitochondrial membrane potential and ROS overproduction (from the malfunctioned mitochondria) are the major mechanisms for arsenic toxicity and that mitochondria is supposed to be a specific target for its toxicity. 37,42 Arsenic is metabolized (methylated) in rodents. Monomethylarsonous acid, one of the metabolites, which distrib- Arsenic Nanoparticles-induced Hepatotoxicity ute irregularly in different tissues (RBC, liver, and kidney), is an ultimate toxicant to mitochondria.…”
Section: Discussionmentioning
confidence: 99%